2019
DOI: 10.1002/spp2.1263
|View full text |Cite
|
Sign up to set email alerts
|

New biological insights into the Middle Triassic capitosaurs from India as deduced from limb bone anatomy and histology

Abstract: Multiple limb bones of different Middle Triassic capitosaurs from India including Cherninia denwai and Paracyclotosaurus crookshanki were examined to reveal differences in palaeobiology and lifestyle adaptations. Limb bone anatomy of Cherninia is characterized by distinct torsion and its absence in the fore and hindlimb bones, respectively. Substantial torsion is seen in all the limb bones of P. crookshanki. Woven fibred bone tissue, a very rapidly deposited tissue mostly seen in the embryos and very young ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 107 publications
(219 reference statements)
0
5
0
Order By: Relevance
“…Studies including osteohistological research on Indian temnospondyls are rare (Ray, Mukherjee & Bandyopadhyay, 2009;Mukherjee, Ray & Sengupta, 2010;Mukherjee, Sengupta & Rakshit, 2020). Ray, Mukherjee & Bandyopadhyay (2009) provided preliminary results on the osteohistology of limb bones, ribs, and intercentra of three temnospondyl taxa from different Indian Triassic localities.…”
Section: General Temnospondyl Osteohistologymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies including osteohistological research on Indian temnospondyls are rare (Ray, Mukherjee & Bandyopadhyay, 2009;Mukherjee, Ray & Sengupta, 2010;Mukherjee, Sengupta & Rakshit, 2020). Ray, Mukherjee & Bandyopadhyay (2009) provided preliminary results on the osteohistology of limb bones, ribs, and intercentra of three temnospondyl taxa from different Indian Triassic localities.…”
Section: General Temnospondyl Osteohistologymentioning
confidence: 99%
“…In the study by Mukherjee, Sengupta & Rakshit (2020), a larger dataset was analyzed histologically including 17 limb bones ranging from juvenile to adult ontogenetic stages. The studied taxa included Middle Triassic capitosaurids, such as Cherninia denwai (nine limb bones), Paracyclotosaurus crookshanki (five limb bones) and an indetermined capitosaurid (five limb bones).…”
Section: General Temnospondyl Osteohistologymentioning
confidence: 99%
“…Indeed, finite element analysis (FEA) of various stereospondyls to infer feeding behavior has identified the potential for ecological differentiation among the distinct morphotypes (e.g., Fortuny et al, 2011, 2012, 2016, 2017; Lautenschlager et al, 2016; Konietzko-Meier et al, 2018). Additionally, an increasing body of histological literature has identified disparate physiological capabilities and growth patterns among closely related taxa (e.g., Konietzko-Meier and Klein, 2013; Muhkerjee et al, 2020), indicating differing responses to local environmental conditions. Metoposaurids are actually the best sampled clade in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies do hint at cryptic ecological and physiological differentiation that could in turn explain the different geographic ranges of various clades. Muhkerjee et al (2010, 2020) suggested that some paracylotosaurid capitosaurs were more terrestrially capable than other stereospondyls, perhaps indicating a more shallow-water spatial occupation when in water. Some differences could also relate to the tolerance of various taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The lower Denwa comprises multistoried, sheet-like medium-fine grained sandstone bodies interleaved with red mudstones, while the upper Denwa is a mudstone-dominated unit characterized by layers of ribbon-shaped channel-fill bodies and sandy to heterolithic sheet sandstones encased within the mudstones. The vertebrate assemblage (Table 1) includes the ceratodontid Ceratodus, the capitosaurs Paracyclotosaurus, Cherninia, and three indeterminate taxa, the undescribed brachyopid, the lonchorhynchine trematosaurid, an undescribed rhynchosaur, and various medium-large dicynodonts (Mukherjee and Sengupta, 1998;Bandyopadhyay and Sengupta, 1999;Mukherjee et al, 2019). Recently the horned allokotosaur Shringasaurus (Fig.…”
Section: Middle Triassicmentioning
confidence: 99%